THE EFFECT OF FOOT SOAK THERAPY USING WARM WATER TOWARD ANXIETY LEVEL OF PREECLAMPSIA MOTHERS IN PUBLIC HEALTH OF TEMPUREJO JEMBER REGENCY - Rhozy Sadya Mangrasih; Dini Kurniawati; Peni Perdani Juliningsih (Journal of Nursing Science Update (JNSU), 2020)
One of psychological error happened on preeclampsia mothers is anxiety disorder. One of the interventions given to preeclamptic women who suffer anxiety is the treatment of warm water foot soak. The research aim to analyze the effect of warm water foot soak therapy on anxiety of preeclampsia women in Puskesmas Tempurejo, Jember Regency. This research used Quasi experimental with a research design of Pretest-posttest with Control Group. The sample was 30 preeclamptic women and used purposive sampling. Data was obtained using an anxiety questionnaire (validity value 0.93 and reliability value 0.97). Data analysis used Wilcoxon. The results of this research showed that there were 15 effects of warm water foot soak therapy (p = 0,003). While in the control group there was no influence (p = 0.317). The mann whitney Â showed significant differences between the intervention groups after being given warm water foot soak therapy and the control group (p = 0,000). Warm water foot soak therapy is a non-pharmacological therapy that can stimulate the endorphin hormone so that the body feels relaxed. The effect of relaxation by increasing comfort through sensations on foot surface and lower the level of anxiety. This warm water foot soak therapy is applicable for pregnant women who suffer anxiety.Â